The young sea officer's sheet anchor, or, A key to the leading of rigging, and to practical seamanship - Lever, Darcy, 1760?-1837. (New York : Edward W. Sweetman Co., 1963)
"In this book there is no attempt at any thing new, what may not have been treated on before, or with which every good seaman is not perfectly acquainted. It is intended solely as a Key to the leading Rigging and to practical Seamanship; as an Assistant to render the knowledge of them easy and familiar to the young Gentlemen of the Royal Navy, the Honourable East India Company's Service, and others who may not have been long enough at sea, or have had an opportunity of acquiring it by practice."--Page v
Errata slip inserted.
Facsimile of the first Philadelphia from the second London edition, 1819.
With an appendix containing several figures illustrative of novelties and improvements in rigging.
Mode of access: Internet.
Keywords: Navigation; Masts and rigging; Gréement.; Navigation; Masts and rigging; Navigation